Self-esteem formation among people who are in rehabilitation for drug abuse in Bangli Mental Health Hospital, Bali, Indonesia - Mde Dewi Sariyani; Ni Komang Ekawati; Dyah Pradnyaparamita Duarsa; Kadek Sri Ariyanti (Intisari Sains Medis, 2019)
Background: Self-esteem formation is an essential aspect for people who use drugs to support the success of a rehabilitation program, and to prevent ongoing relapse. However, self-esteem formation is not a priority in the rehabilitation program. It also tends to ignore the drug abuse status and psychological states of its clients. This study aimed to explore self-esteem formation among people who are in rehabilitation for drug abuse at the Bangli Mental Health Hospital. Findings from this study provide insights to the hospital on the importance of self-esteem formation through a rehabilitation program.Metode: A qualitative study was conducted in the Bangli Mental Health Hospital. We recruited a total of ten informants purposively who are in a rehabilitation program for at least two weeks for drug abuse at the Darmawangsa Ward Bangli Mental Health Hospital. Data were collected through in-depth interviews. Data were analyzed inductively and were presented using a narrative approach.Results: Our in-depth interviews found that self-esteem formation among people who are in rehabilitation for drug abuse depends on various factors such as family support, peer support, life experience, skills and traits, spirituality, policies, parenting history, physical and social environments.Conclusion: Self-esteem formation is determined by various factors and the drug abuse status of informants. We hope that the Bangli Mental Health Hospital can provide rehabilitation services tailored for every drug abuse status during their recovery time at the rehabilitation center.